Effect of Nanoclay on Thermal Properties of Polylacticacid-Kenaf Hybrid Bio-composite - Kaiser, Mohammad Rejaul; Anuar, Hazleen (2011)
An alternative composite material which is a mixture of bio-fiber with nano filler and polymer known as hybrid bio-composite has become a state of the art in composite research and development. The hybrid bio-composite has been widely studied with different combinations for the application of secondary structure in automotive industry, packaging, aerospace, sports, armour proucts and others. The availability of natural fiber (such as kenaf fiber) makes the hybrid bio-composite competetively lower cost and feasible to be produced industrially for wide range of applications. The main objectives of this paper are to fabricate and the effect of nanoclay on thermal properties of hybrid bio-composite. A comprehensive database was developed to determine the thermal property of PLA, PLA-20KF-3Clay, PLA-20KF-5Clay and PLA-20KF-7Clay. Three point bend Dynamic mechanical analysis (DMA) tests were carried out on standard specimens at temperature ranging from -900C to 1000C whereas frequency was 1Hz. The result revealed that with addition of nanoclay glass transition temperature (Tg) increased 50C. The storage modulus (E’), loss modulus (E”) and damping (tanδ) also increased with addition of nanoclay which is an indication of better thermal properties.